Nuclear accumulation of mutant p53 protein: A possible predictor of failure of intravesical therapy in bladder cancer - (:unkn) unknown (BLACKWELL SCIENCE LTD, 1997)
Objective To investigate the expression and importance of the nuclear accumulation of p53 in superficial transitional cell carcinoma (TCC) of the bladder and its role as a predictor of response to treatment. Patients and methods Tumour samples from 30 patients (two women and 28 men, mean age 60.1 years, range 44-75) with pTa/pT1 tumours were assessed immunohistochemically using the Pab1801 monoclonal antibody and standard avidin-biotin peroxidase staining for p53 protein. Results Tumours from six patients (20%) showed nuclear accumulation of p53; five of these patients failed intravesical therapy with bacille Calmette-Guerin (BCG) and progressed to muscle invasive and/or metastatic disease, in contrast to six of 24 patients with no detectable nuclear oncoprotein. Conclusions The nuclear accumulation of p53 appears to be a prognostic indicator of tumour unresponsive to intravesical treatment, even with the most potent agent (BCG). Therefore, early radical treatment modalities must be seriously considered in this group of patients.
Keywords: bladder neoplasms; p53; tumour-suppressor gene; BCG therapy; CARCINOMA IN-SITU; TUMOR PROGRESSION; EXPRESSION; GENE; OVEREXPRESSION; MUTATIONS; STAGE